Kewenangan Pemerintah dalam Pembubaran Organisasi Kemasyarakatan - I Gde Pasek Ari Krisnadana; I Gusti Bagus Suryawan; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2022)
Ormas, which are familiarly referred to as community organizations, are organizations that exist and are formed from the community voluntarily based on the same needs, interests, common aspirations, activities and goals in participating in development for the sake of the Unitary State of the Republic of Indonesia based on Pancasila. The purposes of this study are to reveal the scope of government authority in the dissolution of civil society organizations in Indonesia and the mechanism for the dissolution of civil society organizations in Indonesia. The research method used is normative legal research with a statutory approach. Sources of legal materials used in the form of secondary and primary legal sources through recording and documentation studies in which legal materials and data are managed using interpretive analysis. The results of the study indicate that the scope of government authority in the dissolution of community organizations is based on the attribution authority. Regarding the mechanism for dissolving community organizations, it refers to the provisions of Law Number 16 of 2017 concerning Ormas. The author suggests that the government always conduct socialization and supervision related to the activities of community organizations so that the community and mass organizations must be guided by the 1945 Constitution of the Republic of Indonesia and Pancasila because it is the most important principle in establishing community organizations.